A bibliometric analysis of research trends on the microbiological safety of low-moisture foods - Onyeaka, H.; Anumudu, C.; Miri, T.; Ahmad, N. H. (Rynnye Lyan Resources, 2023)
Research has shown that some pathogens, including Salmonella and other spore-formers, survive and remain viable in low-moisture foods (LMF). This review highlights trends in publication and outlook of the research field, using articles published in Scopus between 2001 to 2020. Systematic article retrieval and data analysis were conducted with the aid of Scopus analytical tools and Excel software. Visualizations of trends in the publication were performed using VOSviewer (1.6.13). A total of 267 articles were published on the microbial safety of LMF, with a rapid rise in the number of publications per year. The U.S. has the highest research output (143 publications), followed by China (35 publications). Washington State University ŽPullman, USA, has the highest number of publications from a single institution, while professor Juming Tang is the author with the highest number of publications. Research on LMF focused on detecting possible microbial contaminants in the foods and exploring the relationship between water activity and microbial survival. Salmonella was identified to be the leading cause of foodborne diseases associated with the consumption of LMF. Overall, newer research focusing on the molecular characterization of microbial contaminants of LMF and approaches to eliminate these pathogens and spoilage agents from LMF.